Enforcement of Human Rights According to Nurcholish Madjid: Fiqh Siyasah Dauliyah Perspective - Syamsuar; Rizki, Darlin; Zikriati (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2024)
Human rights enforcement is often considered a classic issue that lacks appeal, particularly when violations are committed by political elites who attempt to justify their actions. However, discussing the past wrongdoings of a regime remains relevant and crucial as a preventive measure to avoid similar violations in the future. This research explores Nurcholish Madjid's interpretation of Human Rights enforcement from the perspective of Fiqh Siyasah Dauliyah. This study uses a qualitative phenomenological approach to examine Aceh's DOM (Military Operations Area) events from 1989 to 1998. Data were collected through interviews with Aceh community leaders and a thorough review of scholarly literature, including works by Nurcholish Madjid and related sources. The findings reveal the significant relevance of Fiqh Siyasah Dauliyah and human rights in analyzing international issues, particularly in conflict resolution contexts. Reports from the DOM Aceh period highlight extensive human rights abuses, underscoring the need for an effective judicial system to address violations and ensure victim restitution. Nurcholish Madjid advocates for conflict resolution through dialogue and peace, emphasizing the constant protection of civilians. Fiqh Siyasah Dauliyah promotes international dialogue and peace during peaceful times (Dar al-Islam), positioning war as a last resort only after all peaceful measures have failed. During wartime (Dar al-Harb), it insists on maintaining ethical conduct, permissible solely when peaceful alternatives have been exhausted. Islamic principles dictate that military engagements should not cause excessive suffering for civilians and should conclude with a surrender, peace treaty, or ceasefire.